Efficacy and safety of 85% phenol and 4% croton oil solution in the treatment of anogenital penile warts: a proof-of-concept study - Maria Cecília Belli; Hélio Amante Miot; Luis Eduardo Garbers; Bruno Dias Martimiano (Surgical & Cosmetic Dermatology)
Introduction: An 85% phenol and 4% croton oil solution (SFC) has cytotoxic effect on the epithelium; however, it has not been evaluated in the treatment of anogenital warts (AGW). Objective: To evaluate the effectiveness of SFC in the treatment of penile AGW in immunocompetent patients. Methods: Open, uncontrolled clinical trial (proof-of-concept), involving patients with penile AGW treated with SFC and reevaluated after 28 days. RESULTS: We evaluated 16 treatments in 9 participants. SFC promoted total clearance of the lesions in 25% (95% CI 2-48%) of treatments. Conclusions: Although well tolerated, SFC caused insufficient rates of total clearance.